MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) DI SD - Rahmana, Dian (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research is based on the fact that the social learning common dominated by the teacher who always being the sarce of the informations Based on the plan of cycle I, on first meeting is 71% average. Second meeting is  about 85% .  then the second cycle is 96%. The realization of first cycle in first meeting, the teachers aspect is 78% and the students is 75%, second meeting, teacher aspect is 89% and students is 85%. The second cycle teacher aspect is 96% and students is 85%. The study’s result in cycle I on first meeting : koqnitif value 56,4,  affective value 65,7, psikomotor value 76,3. So that, the PBL model is able to use in a reference on learning process.